Selection of the optimal set of revenue management tools in hotels - Korzh, Nataliia; Onyshchuk, Natalia (Technology audit and production reserves, 2017)
The object of research is the scientific category «revenue management» and its tools, which, with the growth of the number of on-line sales channels of hotel services, become decisive in the struggle for survival. The existence of a large number of profit management tools associated with the online booking regime work as a SmallDat and gives quite scattered information about the state of the market. One of the most problematic areas is the formation of perspective analytics using existing tools. In the course of the research methods of analysis, generalization and comparison of existing analytical software on the market were used, influencing the decision on the tactical actions of the hotel in the markets. The author’s interpretation of the scientific category «revenue management» is obtained as an auxiliary method of maximizing profits from a fixed perishable resource based on understanding, forecasting and strategic influence on consumer behavior. The proposed definition has a number of features, in particular, the emphasis is not on revenue growth, but on profits that can be obtained as a result of the implementation of specific strategic actions. The advantages and disadvantages of the analytical tools common in the country are analyzed: Rate Shopper; OTA; BI and RMS. It is proved that no tool provides perspective analysis and therefore it is necessary to use several tools. Since this is an economic issue, the hotel must have an optimal set of such tools for the development of strategic decisions. A model is proposed for making managerial decisions to optimize a set of analytical tools, which demonstrates the progress of the decision-making process for working with the instrument. According to the model, each hotel can choose at its discretion a set of analytical tools and check their relevance in the operational cycle of the hotel and informative for development of strategic decisions.